Is it worth to give steroid in caudal epidural injections? A prospective randomized controlled study - Kumar, S.; Singh, S.; Verma, R. (Scientific Journal of Medical Science, 2014)
Background: Epidural injection, besides surgical decompression, is now one of the most common modality of treatment in lumbar disc herniation who doesn’t responds to conservative therapy. The main aim of our study was to evaluate the role of fluoroscopically guided caudal epidural injection with or without steroids in patients of one or two level lumbar disc herniation. Material and methods: Two groups were made group N and group S. Each patient in group S received 2 ml (80 mg) of methyl prednisolone mixed with 10 ml of lignocaine (2%) and diluted in 18 ml of normal saline and group N received 10 ml of lignocaine (2%) with 20 ml of normal saline. A total of 3 caudal epidural injections were given to each patient at an interval of 3 weeks. All patients were prospectively assessed with examination of straight leg raising, visual analogue scale pain scores and Oswestry Disability Scale at 1, 3, 6, 9, 12 month interval. Results: No statistically significant differences were observed in the baseline scores between the 2 groups. At follow up, Pain scores, ODI and SLR changed significantly from baseline in both groups, with no significant differences between the two groups except at the 1 month where decrease in VAS and ODI Score was significantly more in group S. No patient reported any major immediate or late complication(s) following caudal epidural injection. Conclusion: Normal saline or saline mixed with steroid provides same benefit at long term but at one month steroid group patients showed more relief as compared to saline group.